N-Heterocycle derivatives: An update on the biological activity in correlation with computational predictions - Sahar Saleh Alghamdi, Rasha Saad Suliman, Rawan Awadh Alshehri, Razan Suleiman Almahmoud, Renad Ibrahim Alhujirey (Journal of Applied Pharmaceutical Science, 2022)
This study focuses on selected potent N-heterocycle scaffolds, including oxazolone, oxazole, and oxadiazole. Numerous studies have examined their biological activity against cancer, infectious diseases, and, importantly, inflammation. Thus, efforts have been made to computationally predict and investigate the drug-like properties of these reported N-heterocycle derivatives. In this study, 19 articles have been reviewed for anticancer, antimicrobial, and anti-inflammatory activity of N-heterocycle compounds. The most potent compounds were examined for their pharmacokinetic properties and drug-like properties using the SwissADME web server. Moreover, a target prediction was performed using the Molinspiration web server to predict possible biological targets. A total of 30 compounds were selected for their potent biological activity as determined by IC50, minimum inhibitory concentration, and edema inhibition for cancer, infection, and inflammation, respectively. Our computational predictions showed that all compounds have the recommended molecular weight except for C5, C6, and I5. Furthermore, the C2, C3, C8, M1, M2, M4, I1, and I4 compounds are expected to have blood–brain barrier permeability, suggesting central nervous activity. Additionally, most of the compounds showed acceptable gastrointestinal absorption. Target prediction studies suggested that compounds could modulate their biological responses via channel modulators and receptors to different degrees. The selected N-heterocycle derivatives possess promising medicinal properties that could be utilized for future drug discovery.
Keywords: Oxazolone, oxazole, oxadiazole, benzoxazole, pharmacokinetics, target prediction